(untitled) (Desenvolvimento em Questão, 2025)
The article analyzes the process of metropolization in Marabá, highlighting its historical, socio-economic, and spatial evolution as a regional hub in southeastern Pará and within the Carajás Integration Region. Originally based on vegetal and mineral extractivism, the municipality underwent significant transformations from the developmental projects of the 1960s and 1970s, which spurred infrastructure, industrialization, and migratory flows. The study investigates how historical, economic, and political factors contributed to the consolidation of Marabá as a metropolitan center and the contemporary challenges arising from this trajectory, such as social inequality, environmental vulnerability, and the lack of integrated urban planning. Aiming to map the historical and socio-economic trajectory, identify structural factors of metropolization, and provide methodological support for future research, the study adopted a qualitative, descriptive, and exploratory approach, integrating literature review, documentary analysis, and secondary data while articulating historical, social, economic, and environmental perspectives. The results indicate that the city developed a poly-nucleated urban pattern, marked by population and economic flows that reflect both advances and contradictions of the regional development model, underscoring Marabá’s importance in the Amazonian context and providing insights for sustainable public policies that consider the city’s specificities and potential.